2014
DOI: 10.3109/09513590.2014.911278
|View full text |Cite
|
Sign up to set email alerts
|

Are the new IADPSG criteria for gestational diabetes useful in a country with a very high prevalence?

Abstract: The International Association of Diabetes and Pregnancy Study Groups released new recommendations on screening methods and diagnostic criteria for gestational diabetes. The main objectives of the present study were to analyze characteristics of mothers who underwent the new screening test, and to assess the prevalence of gestational diabetes and related pregnancy complications such as the 5-minute Apgar score <7, in a urban maternity clinic in Djibouti. The effect of treating gestational diabetes was also eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Of the 44 993 studies identified, 156 studies,2324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsunclassified
“…Of the 44 993 studies identified, 156 studies,2324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsunclassified
“…After applying our inclusion and exclusion criteria, we ended up with 33 eligible articles [2124, 33–61] for inclusion in this systematic review. Of these, 28 papers contributed towards estimation of GDM prevalence [21, 23, 24, 33–38, 40–42, 4655, 5761], 20 towards assessment of risk factors of GDM [2124, 39, 41, 44, 45, 4750, 5255, 57, 58, 60, 61] and 6 towards the evaluation of the impacts of GDM on maternal and offspring outcomes [39, 43, 47, 51, 57, 61].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Cameroon [23, 47] and Ethiopia [22, 38] contributed two studies each. The other 7 countries (Democratic Republic of Congo [46], Djibouti [51], Ghana [53], Kenya [56], Rwanda [55], Uganda [57] and Zimbabwe [60]) contributed one study each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation